Wanted: Elevator Man - Peterson, Joseph G. (Book collections on Project MUSE., 2012)
"A profound but comedic meditation on failure in this life, how one comes to terms with not achieving one's dreams, the nature and origin of such dreams, and the meaning of the American dream itself"--